Efficiency of plant-based acaricide gels compared to fluvalinate-impregnated strips for control of Varroa destructor in honey bee colonies - Khajehali, Jahangir; Poorjavad, Nafiseh; Bolandnazar, Alireza; Shahim-Germi, Farid; Kimiaie, Mahyar; Ardestani, Masoud M (Experimental & applied acarology, 2023)
The Varroa mite is one of the most important pests of honey bee colonies. This study compares the efficiency of thymol-based acaricides with the tau-fluvalinate-based commercial treatment to control this mite species. Two experiments were conducted: (1) in the Fall, thymol-based gel was compared with a widely used acaricide, fluvalinate-impregnated strips (Apistan®), and (2) in the Spring, gels containing thymol-only, thymol + menthol + eucalyptus essential oil, and thymol + thyme essential oil were compared with fluvalinate-impregnated strips. In the first experiment, both treatments reduced Varroa mite infestation levels significantly after 70 days of their application compared to the control treatment. The results of the second experiment showed that thymol + thyme essential oil gel, thymol + menthol + eucalyptus essential oil gel, and Apistan strips had always higher efficiency on decreasing mite infestation levels of the selected colonies compared to the control treatment and thymol-only gel during their 7-week application. The results of this study demonstrate that plant-based acaricides for controlling Varroa mites in honey bee colonies have similar efficiency compared to the chemical control methods. Therefore, it is better to use these selected acaricides to reduce mite resistance to chemical control treatments in honey bee colonies.
Keywords: Gels; menthol; akaricidy; infestace roztoči; thymol; Bees; Thymol; Eucalyptus; včely; Oils, Volatile; Animals; oleje prchavé; Essential oils; zvířata; Menthol; Apis mellifera; gely; Apistan; Varroidae; Acaricides; Mite Infestations